'But they're happening to you at the wrong time': Exploring young adult women's reflections on serious illness through photovoice. (September 2013) - Burles, Meridith; Thomas, Roanne
Although serious illness is often associated with aging, many young adults are affected by various life-threatening and chronic illnesses, and thus have experiences that do not correspond to socio-cultural expectations for young adulthood. In this article, we describe a qualitative study exploring young adult women's experiences of serious illness. Ten participants diagnosed with a life-threatening or chronic illness in the previous three years participated in phenomenological interviews and photovoice project that focused on what it is like to be seriously ill during young adulthood. Our analysis reveals that participants experienced serious illness with respect to their position in the life course; specifically, participants perceived ill health as being inconsistent with young adulthood. This finding is illustrated by three inter-related themes: feeling abnormal and 'off time, ' realizing vulnerabilities, and renegotiating expectations for young adulthood and the future. We propose that these themes offer evidence of how illness is experienced within the broader socio-cultural context of individuals' lives. We conclude that social workers involved in supporting this population are well positioned to address life course disruptions brought about by illness and aid in negotiating ill health with respect to expectations for young adulthood.